Fifth Five Year Plan Uttar Pradesh Volume I Planning Department, Uttar Pradesh - Planning Commission (Planning Commission, 1973)
The National Plan envisages that oven with the expanded, opportunities of employment in the Fifth Plan, the poor will not be able to buy for themselves all the essential foods and services, which should figure in any reasonable concept of a minimum standard of living. These measures have, therefore, to be supplemented, upto at least a certain minimum level, by items of social consumption, like education, health, nutrition, drinking water, housing, communications, environmental sanitation and electricity. the provision of these basic facilities has been accented as the National programmes of minimum needs.
Planning Department, Uttar Pradesh